Unveiling Critical Thinking Skills of Students in Top Junior High Schools in Makassar: An Empirical Study - Sitti Rahma Yunus; Sitti Saenab; Andi Rahmat Saleh; Anisya Rahmaniah Nasra; Iqra Ramadani (Al Jahiz, 2025)
This study aims to describe the critical thinking skills of eighth-grade students attending public junior high schools with an A accreditation rating in Makassar City. The population of the study consisted of 4,167 students, and a sample of 365 students was selected using a cluster random sampling technique. The sample was drawn from 13 public junior high schools in Makassar City. The research instrument used was a critical thinking skills test in the form of 24 multiple-choice questions. Based on the results of the descriptive statistical analysis, the critical thinking skills of eighth-grade students in A-accredited public junior high schools in Makassar City were found to be in the moderate category, with an average percentage of 65.35%. Specifically, critical thinking skills on the elementary clarification indicator were in the high category (70.50%), basic support was in the low category (53.63%), inference was in the moderate category (60.32%), advanced clarification was in the high category (68.56%), and strategy and tactics was also in the high category (73.77%).